1999
DOI: 10.1046/j.1365-3040.1999.00509.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ethylene biosynthesis by antisense ACC oxidase RNA prevents chilling injury in Charentais cantaloupe melons

Abstract: Non‐freezing low temperature storage causes injury to melons and most other fruit and vegetables of tropical and subtropical origin. We demonstrate here that ethylene suppression through an antisense ACC oxidase (ACO) gene considerably reduced the sensitivity of Charentais cantaloupe melons to chilling injury. In contrast to wild‐type fruit, antisense ACO melons did not develop the characteristic chilling injury of pitting and browning of the rind neither when stored at low temperature (3 weeks at 2 °C) nor up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0
13

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(93 citation statements)
references
References 41 publications
9
71
0
13
Order By: Relevance
“…This may be due to heat-induced ethylene in association with low temperature that would have lowered the SOD activity. These results are in corroboration with the observations made indicating that ethylene, in association with low temperature, lowered the SOD activity [24]. Whereas SOD activity differences in the T 1 , T 2 and T 5 (pre-cooling at 8 ºC and 13 ºC and control) were significantly different from those of T 3 and T 4 (heat shock followed by cooling at 8 ºC and 13 ºC).…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to heat-induced ethylene in association with low temperature that would have lowered the SOD activity. These results are in corroboration with the observations made indicating that ethylene, in association with low temperature, lowered the SOD activity [24]. Whereas SOD activity differences in the T 1 , T 2 and T 5 (pre-cooling at 8 ºC and 13 ºC and control) were significantly different from those of T 3 and T 4 (heat shock followed by cooling at 8 ºC and 13 ºC).…”
Section: Discussionsupporting
confidence: 92%
“…Chilling injury due to chilling stress induced ethylene production which in turn might have reduced the level of POX in control fruits and these results were found to be in concordance with those of BenAmor et al and Maria et al [19,21] who reported ethylene reduced POX activity in chilled cantaloupe melons and Fortune mandarins.…”
Section: Discussionsupporting
confidence: 90%
“…Ethylene suppression in antisense ACO melons considerably reduced the sensitivity to chilling injury [50,51]. Treating transgenic melons with ethylene resulted in the restoration of chilling sensitivity.…”
Section: Chilling Injurymentioning
confidence: 96%